(untitled) (Journal of Hama University, 2023)
The aim of the current research is to identify the attitudes of psychological counselors towards electronic counseling. The differences in the attitudes of psychological counselors towards electronic counseling are defined according to the variables (sex, number of years of experience, educational qualification, and training courses in the field of psychological counseling). The analytical descriptive approach was used, and the sample consisted of (277) male and female psychological counselors from Hama governorate schools in the basic and secondary education stages. A questionnaire was used as a research tool consisting of 25 items, and the research reached the following results: • The psychological counsellors’ attitudes towards electronic counseling were positive. • It was found that there were no statistically significant differences in the attitudes of psychological counselors towards electronic counseling, according to the variables of gender, number of years of experience, academic qualification, and training courses in the field of psychological counseling.